How Does the Traffic Community Education Unit (Dikmas Lantas) Reduce Student Traffic Violations? - Hanna Widya Sari (Advances in Police Science Research Journal, 2021)
The background of this research is the high number of traffic violations at the Karawang Police. Based on data from the Karawang Police Traffic Unit, where the number of traffic violations by high school students. So a research was carried out aimed at reducing traffic violations by high school students at the Karawang Police. The purpose of this study was to describe a general description of traffic violations and describe the efforts made by the Dikyasa Unit with the Dikmas Lantas program. The theory used as an analysis knife to discuss this research, using several theories and concepts is management theory, communication theory, effort concept, Dikyasa Unit concept, Dikmas Lantas concept, traffic violation concept, and student concept. In this study using a qualitative approach and the method used is field research (field research) and data collection techniques by interview, observation, and document review. The results of the study found that the Karawang Police had a high number of violations committed by high school students. The efforts made by the Dikyasa Unit in reducing traffic violations have decreased. Factors that influence the efforts of Dikmas Lantas are internal factors including Human Resources, commitment, budget, facilities and infrastructure. Meanwhile, external factors include legal awareness, culture, media, coordination. Based on the discussion of the results of this study, according to the author, there are several things that must be done, including (1) increasing the number of Dikyasa Unit members, (2) involving officers in training, (3) making daily activity plans, (4) improving Lantas Training.